Crop evapotranspiration methodology and application in Mediterranean region - Rana G.; Katerji N. (WEMED workshop: how to advance the knowledge on water use efficiency in the Mediterranean region ?, 2007)
This study analyses methods for measuring and estimating ET in the particular conditions of the Mediterranean region. The first part of the work presents the ET measurement methods, at plant and canopy scale. In particular for the canopy scale, we illustrate the direct method (weighing lysimeter) and the indirect methods (micrometeorological techniques, hydrological approaches). For these methods advantages and disadvantages are given for the use in the Mediterranean region, together with the precautions to be used for minimizing the measurement errors. The second part of the study presents methods to estimate the ET; the methods are divided in direct (the Penman-Monteith one step technique) and indirect (mainly the Kc approach). The Penman-Monteith method is analysed and a model of canopy resistance is presented in detail. This model was developed in three steps: for crops under well watered conditions, for crops under water stress and a multi-local tests. Here the good performances of this model are presented for a Mediterranean site (South Italy). Lastly, the Kc-approach for determining ET is presented. Here we demonstrate that this method does not work properly in Mediterranean region for two reasons: the canopy resistance for the reference grass can not be considered as constant and the values of the crop coefficients can be very different in different sites for a given crop. In conclusions some suggestions for the future research needs are given for the different methods of determining ET in Mediterranean region.
Workshop on: How to Advance the Knowledge on Water Use Efficiency in the Mediterranean Region ? 2006/10/26-28, Valenzano (Italy)